Exosomes in Cancer Radioresistance - Ni, Jie; Bucci, Joseph; Malouf, David; Knox, Matthew; Graham, Peter; Li, Yong (Frontiers in Oncology, 2019)
Radiation is a mainstay of cancer therapy. Radioresistance is a significant challenge in the treatment of locally advanced, recurrent and metastatic cancers. The mechanisms of radioresistance are complicated and still not completely understood. Exosomes are 40–150 nm vesicles released by cancer cells that contain pathogenic components, such as proteins, mRNAs, DNA fragments, non-coding RNAs, and lipids. Exosomes play a critical role in cancer progression, including cell-cell communication, tumor-stromal interactions, activation of signaling pathways, and immunomodulation. Emerging data indicate that radiation-derived exosomes increase tumor burden, decrease survival, cause radiation-induced bystander effects and promote radioresistance. In addition, radiation can change the contents of exosomes, which allows exosomes to be used as a prognostic and predictive biomarker to monitor radiation response. Therefore, understanding the roles and mechanisms of exosomes in radiation response may shed light on how exosomes play a role in radioresistance and open a new way in radiotherapy and translational medicine. In this review, we discuss recent advances in radiation-induced exosome changes in components, focus on the roles of exosome in radiation-induced bystander effect in cancer and emphasize the importance of exosomes in cancer progression and radioresistance for developing novel therapy.